STRATEGI KOMUNIKASI PEMASARAN TERPADU KOPERASI SERBA USAHA: TRANSFORMASI KOPERASI SIMPAN PINJAM BUAH KETAKASI MENJADI KOPERASI SERBA USAHA - Kurniawan, Putra (MEDIAKOM, 2024)
This research aims to elaborate on the integrated marketing communication strategy developed by Ketakasi Fruit Multipurpose Cooperative to maximize the potential of its superior product, coffee plantations. The research method used is qualitative descriptive to obtain as much data as possible using data collection techniques through in-depth interview and literature reviews. The result is that there are several strategies which are elaborated through four integrated marketing communication points, which is direct marketing by online, sales promotion, personal selling, and word of mouth. There are four points of integrated marketing communication strategy that emerge through, (1) introducing products online, (2) displaying processed products at production center location, (3) explaining product details to potential buyers at the location, (4) participating in exhibition activities, and (5) strenghen branding. These strategies make Ketakasi Fruit Multipurpose Cooperative able to empower the community and develop coffee products so that they can improve the welfare of the Sidomulyo community in general.